The photocatalytic degradation of methylene blue using bismuth vanadate (Bi2VO5.5) powder - Jitreephan Phanmalee (2018)
© 2017 Trans Tech Publications, Switzerland. Bismuth vanadate (Bi2VO5.5) powder has been successfully prepared by microwave method. Bismuth nitrate and ammonium vanadate were used as the starting precursors with the mole ratio of 2:1 in 2-propanol. The microwave power was 500 Watt for 2-6 min. The yellow powder was obtained and calcined at 500°C for 2h. The structure was identified by X-ray diffraction (XRD). The morphology was investigated by field emission scanning electron microscopy (FESEM). The chemical composition was determined by energy dispersive X-ray spectrometry (EDXS). The functional groups were investigated by fourier transform infrared spectrometry (FTIR). The photocatalytic degradation of methylene blue (MB) using Bi2VO5.5powder was studied by ultraviolet-visible spectrophotometry (UV-Vis).